PENINGKATAN KEMAMPUAN PEMAHAMAN MATEMATIS PADA KONSEP PENJUMLAHAN DUA BILANGAN CACAH MELALUI PERMAINAN ULAR TANGGA PADA SISWA SD KELAS I - Sri Mulyani, - (2022)
This research is motivated by the limited media for learning mathematics in schools. This has an impact on the low ability of students to understand concepts so that it affects students' low mathematics learning outcomes as well. The game of snakes and ladders in the material for adding two whole numbers to grade 1 Elementary School is a solution to overcome problems that arise in schools. The purpose of this study was to improve mathematical understanding of the concept of adding two whole numbers to elementary school students in grade 1. The method used in this study was an experiment with one group pretest posttest design. The population in this study were first grade students at SDN Sukamulya. Techniques in collecting data in this study are observation, interviews, tests, and documentation, while the instrument used is a test question in the form of a description. Analysis of quantitative data using Microsoft Excel 2016 and SPSS 24 program. The results of the study revealed that the snake and ladder game in increasing mathematical understanding of the concept of adding two whole numbers through the snake and ladder game in elementary school students in grade I there was an increase in students after learning through the snake and ladder game.